Powrot do gniazda : powiesc z podan XVI w. - Kraszewski, Jozef Ignacy, 1812-1887. (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1986)
An historical novel of the 16th century Poland.
Keywords: Poland -- History -- 16th century -- Fiction